MODEL PENGEMBANGAN SEJARAH BERBASIS NILAI-NILAI RESOLUSI KONFLIK UNTUK MENINGKATKAN HARMONISASI DALAM MASYARAKAT KERINCI - Firza, F.; Joebagio, Hermanu; Wasino, W. (Sebelas Maret University (UNS), 2016)
conflict resolution is a form of culture that exists in the community. In the Kerinci community conflict resolution called mandawah. Conflict resolution contained in the traditional values that are relevant to people's lives, so it is appropriate in a learning model developed especially in the subjects of history. The aim of research to develop models of teaching history values-based conflict resolution to improve harmonization in the Kerinci community life. This study uses research methods Research and Development. Following ten steps development Borg and Gall, simplified into three stages, namely the preliminary study, the development and effectiveness. The study was conducted at SMAN 4 Kerinci, using class XI IPS 1 as an experimental class, while the class XI IPS 2 as a control. Research was conducted in the second semester of the 2015/2016 academic year.The result of the effectiveness of achievement (cognitive) show that the ability of learners between control class and experimental class have significant differences. It was shown that the results of T test with significance level 0.067 1.864 greater than 0.05 (0.067> 0.05). Then the experimental and control class has a variant that is not equal to the average of competence that is not the same. T test for the assessment of the attitude obtained 3.130 with 0.003 significance level less than 0.05 (0.003 <0.05), then Ho is rejected. So mean before and after treatment are not the same experimental class. This means that there is a significant influence on history-based learning model values to improve the harmonization of conflict resolution in the Kerinci community life. Thus the model development history learning values-based conflict resolution effective to improve learning outcomes and harmonization in Kerinci community.